“Me conta mais da tua paixão”: as histórias da paixão de Cristo em Canudos de Belém - Pará - NEVES, Artur Coelho das (2018)
This work has as object of research the spectacle of the Passion of Christ, staged by the Aldeato Group in Canudos, during the holy week in the city of Belém. The group, founded 32 years ago, stands out in the Pará scene for its trajectory signed in a compromise Social and artistic life in the city. This work intends to tell the stories that cross the Passion of Christ in Canudos throughout its existence, through the testimonies of the involved subjects. It relates to the research of Professor Karine Jansen and to Professor HumbertoJardel - Belem’s passionate article (JANSEN - 2003);Hybridism in the Passion of Christ (MELO - 2009),and also the references to the personal reports of participants and former participants.